2007
DOI: 10.1007/s10499-006-9071-0
|View full text |Cite
|
Sign up to set email alerts
|

Masculinization of Convict Cichlid (Cichlasoma nigrofasciatum) by immersion in Tribulus terrestris extract

Abstract: We have examined the effects of Tribulus terrestris (TT), a non-toxic herb, on sex reversal in the Convict Cichlid Cichlasoma nigrofasciatum with the aim of introducing a new environmentally friendly method for masculinization in C. nigrofasciatum. TT is a natural plant product that elevates the testosterone levels in humans and animals. Different concentrations (0.0, 0.10, 0.20 and 0.30 g/l) of TT extract were tested for their effect on sex reversal in C. nigrofasciatum by immersing newly hatched offspring on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 30 publications
3
11
0
3
Order By: Relevance
“…A dose-dependent increase in percentage of males was observed for all the solvent extracts of M. pruriens seed, while fish fed diets containing only methanol and successive methanol extracts of A. racemosus roots showed such dose dependent increase in percentage of males (Table 1). Such dose dependent masculinisation effect of plant extracts was also observed in other studies, where percentage of males increased with increase in the Tribulus terrestris concentration in Poecilia latipinna, P. reticulata, Cichlasoma nigrofasciatum and Clarias gariepinus (Kavitha & Subramanian, 2011;Kavitha et al, 2012;Çek et al, 2007a;Çek et al, 2007b;Turan & Çek, 2007). As the highest treatment concentration of 0.2 g/kg feed produced the maximum percentage of males for both the plants, further experiments with increased concentration might be required to achieve 100% sex reversal with these plants.…”
Section: Resultssupporting
confidence: 82%
“…A dose-dependent increase in percentage of males was observed for all the solvent extracts of M. pruriens seed, while fish fed diets containing only methanol and successive methanol extracts of A. racemosus roots showed such dose dependent increase in percentage of males (Table 1). Such dose dependent masculinisation effect of plant extracts was also observed in other studies, where percentage of males increased with increase in the Tribulus terrestris concentration in Poecilia latipinna, P. reticulata, Cichlasoma nigrofasciatum and Clarias gariepinus (Kavitha & Subramanian, 2011;Kavitha et al, 2012;Çek et al, 2007a;Çek et al, 2007b;Turan & Çek, 2007). As the highest treatment concentration of 0.2 g/kg feed produced the maximum percentage of males for both the plants, further experiments with increased concentration might be required to achieve 100% sex reversal with these plants.…”
Section: Resultssupporting
confidence: 82%
“…These results are supported by the findings of Goda () and Yan, Meng, Lee, Wang, and Kim () who reported a growth improvement of Nile tilapia and broiler checking with GE supplementation. Also, Çek, Turan, and Atik () and Turan and Cek () found that using TE by immersion or as a dietary supplementation improved growth performance of African catfish, guppy and convict cichlid fry. Similarly, Iftikhar, Bashir, Anwar, Mastoi, and Shahzad () reported a significant increase in albino rate body weight with DPPG supplementation.…”
Section: Resultsmentioning
confidence: 98%
“…Çek et al. () also reported that all groups of TT‐treated (0.0, 0.10, 0.20 and 0.30 g L −1 ) convict cichlid, C. nigrofasciatum fry exhibited a higher body weight and total length compared to the control group, but only the 0.3 g L −1 TT treatment significantly increased them (Çek et al., ).…”
Section: Discussionmentioning
confidence: 94%
“…Çek et al. () declared that TT treatment is a more effective method than the administration of synthetic hormone in terms of affecting sex reversal. Previous studies in different fish species also reported that TT improved growth performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation